2015
DOI: 10.1111/pce.12504
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the contributions of osmotic and ionic effects of salinity on stomatal, mesophyll, biochemical and light limitations to photosynthesis

Abstract: There are conflicting opinions on the relative importance of photosynthetic limitations under salinity. Quantitative limitation analysis of photosynthesis provides insight into the contributions of different photosynthetic limitations, but it has only been applied under saturating light conditions. Using experimental data and modelling approaches, we examined the influence of light intensity on photosynthetic limitations and quantified the osmotic and ionic effects of salinity on stomatal (LS ), mesophyll (LM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 53 publications
(206 reference statements)
5
63
4
Order By: Relevance
“…The contributions of LB to reducing A in salt‐stressed rice leaves were relatively small (Fig. ), in disagreement with two studies on H. vulgare (Perez‐Lopez et al ) and C. sativus (Chen et al ) under salt stress. This might be explained by a lower C c in the current study than in the other studies.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The contributions of LB to reducing A in salt‐stressed rice leaves were relatively small (Fig. ), in disagreement with two studies on H. vulgare (Perez‐Lopez et al ) and C. sativus (Chen et al ) under salt stress. This might be explained by a lower C c in the current study than in the other studies.…”
Section: Discussioncontrasting
confidence: 81%
“…After 7 days of NaCl treatment, A decreased significantly in LYP9, SY63 and TXZ25 but not in N22. Generally, it is assumed that stomatal closure is the first response to salinity due to osmotic stress (Delfine et al , Delfine et al , Centritto et al , Moradi and Ismail , Chaves et al , Chen et al ). However, we observed that g s , g m and ETR decreased dramatically in some of the genotypes one day after NaCl treatment, and multiple leaf parameters involving biochemical and physiological traits were affected in almost all of the genotypes after 7 days of treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the relative change of A , g sc , g m and J in Eqn can be approximated by the following (Chen et al . ): normaldAAAmaxnormalrnormalenormalfAAmaxref, normaldgnormalsnormalcgscgnormalsnormalcnormalrnormalenormalfgnormalsnormalcgscref, normaldgmgnormalmgmnormalrnormalenormalfgmgnormalmref, normaldJJJmaxnormalrnormalenormalfJJmaxref, where Amaxnormalrnormalenormalf, gnormalsnormalcnormalrnormalenormalf, gmnormalrnormalenormalf and Jmnormalrnormalenormalf are the reference values. The reference maximum values of net CO 2 assimilation rate, stomatal and mesophyll conductance and the rate of electron transport were obtained in +K treatments; therefore, its parameters were defined as standard.…”
Section: Methodsmentioning
confidence: 99%
“…It is also very likely that salt ions accumulate in mitochondria and chloroplasts disturbing electron flow and causing electrons to leak to molecular oxygen, thereby triggering O 2 À production. Apart from loss of ionic homeostasis, the rise in osmotic potential and salts interferes with specific processes like cell expansion, stomata development and stomatal movement (Kumari et al 2014;Chen et al 2015;Z€ orb et al 2015;Geilfus et al 2017) (Fig. 1).…”
Section: Physiology Of Yield Lossesmentioning
confidence: 99%